A Cocatalyst that Stabilizes a Hydride Intermediate during Photocatalytic Hydrogen Evolution over a Rhodium‐Doped TiO2 Nanosheet. (19th June 2018) - Ida, Shintaro; Sato, Kenta; Nagata, Tetsuya; Hagiwara, Hidehisa; Watanabe, Motonori; Kim, Namhoon; Shiota, Yoshihito; Koinuma, Michio; Takenaka, Sakae; Sakai, Takaaki; Ertekin, Elif; Ishihara, Tatsumi
Abstract: The hydrogen evolution reaction using semiconductor photocatalysts has been significantly improved by cocatalyst loading. However, there are still many speculations regarding the actual role of the cocatalyst. Now a photocatalytic hydrogen evolution reaction pathway is reported on a cocatalyst site using TiO2 nanosheets doped with Rh at Ti sites as one‐atom cocatalysts. A hydride species adsorbed on the one‐atom Rh dopant cocatalyst site was confirmed experimentally as the intermediate state for hydrogen evolution, which was consistent with the results of density functional theory (DFT) calculations. In this system, the role of the cocatalyst in photocatalytic hydrogen evolution is related to the withdrawal of photo‐excited electrons and stabilization of the hydride intermediate species; the presence of oxygen vacancies induced by Rh facilitate the withdrawal of electrons and stabilization of the hydride.